2021
DOI: 10.21873/cdp.10039
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Surgery Reduces Risk of Postoperative Complications and Non Cancer-related Survival in Patients Over 80 Years Old With Colorectal Cancer

Abstract: Background: The short- and long-term results from several reports suggest that laparoscopic surgery (LAP) for elderly patients is expected to reduce the risk of complications due to its minimal invasiveness, However, little is known about the effect of LAP on long-term prognosis aside from cancer. Patients and Methods: Eighty-five cases over 80 years old with colorectal cancer whose primary lesions were resected consecutively were enrolled. Risk factors for complications were searched using categorized clinico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Previous studies have revealed that laparoscopic surgery shows evident advantages over conventional open surgery with less surgical trauma, rapid recovery, and comparable survival outcomes, regardless of the age group. For elderly patients with colorectal cancer, laparoscopic surgery significantly reduced the postoperative complications and non-cancer-related death compared to open surgery [ 20 ]. A recent meta-analysis revealed that elderly patients derived apparent benefits from laparoscopic surgery, including less blood loss and shorten hospital stay, as well as equivalent long-term outcomes when compared with open surgery [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that laparoscopic surgery shows evident advantages over conventional open surgery with less surgical trauma, rapid recovery, and comparable survival outcomes, regardless of the age group. For elderly patients with colorectal cancer, laparoscopic surgery significantly reduced the postoperative complications and non-cancer-related death compared to open surgery [ 20 ]. A recent meta-analysis revealed that elderly patients derived apparent benefits from laparoscopic surgery, including less blood loss and shorten hospital stay, as well as equivalent long-term outcomes when compared with open surgery [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, reports on the safety and efficacy of laparoscopic gastrectomy and colorectomy in patients aged ≥80 years have begun to increase. [10][11][12][13] Several reports have shown the safety of LLR for HCC in elderly patients, with noninferiority or superiority of LLR's surgical outcomes in patients over 65 or 70 years of age. 7,[25][26][27][28] However, reports focusing on super-elderly patients aged ≥80 years are very rare.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to prove the safety and effectiveness of laparoscopic surgery in patients aged ≥80 years. In recent years, reports on the safety and efficacy of laparoscopic gastrectomy and colorectomy in patients aged ≥80 years have begun to increase 10–13 . Several reports have shown the safety of LLR for HCC in elderly patients, with noninferiority or superiority of LLR's surgical outcomes in patients over 65 or 70 years of age 7,25–28 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations